Comparison of voluntary disclosure in Singapore. - Chan, Jean Siew Chen. (2008)
This paper reports on the differences in voluntary disclosure adopted by firms listed on the Singapore Stock Exchange between the years 1997/1998 and between two different industries namely, manufacturing and hotels & restaurants.